Proceedings of the International Seminar on Design Methods in Underground Mining 2015
DOI: 10.36487/acg_rep/1511_08_hassell
|View full text |Cite
|
Sign up to set email alerts
|

Dugald River trial stoping, overall hanging wall behaviour

Abstract: Concerns regarding the uncertainty of stope dilution at MMG Limited's Dugald River Underground Mine led to a trial stoping program to acquire full-scale comprehensive geotechnical information and to test the validity of the proposed geotechnical and mining parameters. As part of the trial, a geotechnical instrumentation program was designed to improve the understanding of the rock mass response to the mining of the trial stopes. This included an array of instruments installed from dedicated hanging wall drives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The data used in this paper are from the underground Dugald River mine in Queensland, Australia (Figure 9). Longitudinal and transversal stopes are used to extract the Zn-Pb Ag ore. Stope dimensions can vary depending on the area of the mine but are approximately 25 m high and 15–30 m long (Hassell et al 2015). Stope width varies between 2 and 35 m depending on the thickness of the orebody.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this paper are from the underground Dugald River mine in Queensland, Australia (Figure 9). Longitudinal and transversal stopes are used to extract the Zn-Pb Ag ore. Stope dimensions can vary depending on the area of the mine but are approximately 25 m high and 15–30 m long (Hassell et al 2015). Stope width varies between 2 and 35 m depending on the thickness of the orebody.…”
Section: Case Studymentioning
confidence: 99%
“…Of these 173 stopes, 41 are a part of the north area of the mine and 132 are a part of the south part of the mine. Nineteen stopes were also part of the 2014 trial stoping stage that was conducted to test the validity of the geotechnical and mining parameters (Hassell et al 2015). For the analysis, the 2014 trial stoping, as well as stopes with data quality concerns, has been removed resulting in a total of 130 stopes.…”
Section: Case Studymentioning
confidence: 99%
“…More detailed descriptions of the trial stoping program and outcomes can be found in de Vries et al (2015), Hassell et al (2015a;2015b) and Carswell et al (2015). Key mine design and scheduling parameters were established, including:…”
Section: Trial Stopingmentioning
confidence: 99%
“…The authors in the studies [34], [35] argue that, when adhered to the fastening technology, cable bolts are an effective method to manage ore dilution when mining low-thickness ore deposits by mining systems with an open stope space. D.R.…”
Section: Introductionmentioning
confidence: 99%